Land Use Effects on Soil Health in Semiarid Drylands. Issue 1 (1st August 2018) - Thapa, Vesh R.; Ghimire, Rajan; Mikha, Maysoon M.; Idowu, Omololu J.; Marsalis, Mark A.
Abstract : Core Ideas: Effects of diverse land uses on soil health indicators were evaluated. Conversion to grassland restores soil organic carbon lost due to cultivation. Livestock integration in cropping systems improves soil organic matter storage. Minimizing soil disturbance improves soil structure and thereby reduces soil erosion. Recent interest in improving soil health and resilience recognizes the role soil organic matter (SOM) plays in the living components and the essential functions they provide. A study was conducted to evaluate SOM components, including soil organic carbon (SOC), particulate organic matter, potassium permanganate oxidizable carbon (POXC), inorganic N, and wet aggregate stability as indicators of soil health under grazed native pasture, cropland converted to grassland, conventional‐tilled grazed cropland, and no‐tilled and strip‐tilled croplands with no grazing. The SOC content was 36.9% greater in grasslands than croplands irrespective of grazing management, and POXC/SOC ratio was 41.2% greater in strip‐tilled croplands than other land uses. Soil inorganic N was 270% greater in croplands than grasslands. The wet aggregate stability in conventional‐tilled grazed cropland was 22.6% lower than other land uses. Restoring grasslands and livestock integration have potential to improve soil health and resilience in semiarid drylands through improvements in SOM dynamics.